Win at home and draw away: Automatic formation analysis highlighting the differences in home and away team behaviors - Bialkowski, A.; Lucey, P.; Carr, P.; Yue, Y.; Matthews, I. (MIT Sloan Sports Analytics Conference 2014, 2014)
In terms of analyzing soccer matches, two of the most important factors to consider are: 1) the formation the team played (e.g., 4-4-2, 4-2-3-1, 3-5-2 etc.), and 2) the manner in which they executed it (e.g., conservative - sitting deep, or aggressive - pressing high). Despite the existence of ball and player tracking data, no current methods exist which can automatically detect and visualize formations. Using an entire season of Prozone data which consists of ball and player tracking information from a recent top-tier professional league, we showcase an automatic formation detection method by investigating the "home advantage". In a paper we published recently, using an entire season of ball tracking data we showed that home teams had significantly more possession in the forward-third which correlated with more shots and goals while the shooting and passing proficiencies were the same. Using our automatic formation analysis, we extend this analysis and show that while teams tend to play the same formation at home as they do away, the manner in which they execute the formation is significantly different. Specifically, we show that the position of the formation of teams at home is significantly higher up the field compared to when they play away. This conservative approach at away games suggests that coaches aim to win their home games and draw their away games. Additionally, we also show that our method can visually summarize a game which gives an indication of dominance and tactics. While enabling new discoveries of team behavior which can enhance analysis, it is also worth mentioning that our automatic formation detection method is the first to be developed.